(untitled) (Revista Apotheke, 2021)
There are countless Afro-descendent artists who currently unfold their questions and experiences through art, imbranding their existence as a person and that of an artist together with the work. This text proposes to discuss the construction of the work / artist from a poetics with autobiographical perceptions that addresses ethno-racial issues, starting from individual perceptions going against socio-cultural contexts. For this, we start by contextualizing, and tracing the processes that involve the black population in Brazil, such as miscegenation, and the distances that separate the Afro-Brazilian people from taking possession of their narrative and knowing their past, approaching a poetics that seeks to evoke a approximation to Afro-Brazilian culture. Thus the writing points out the implications from the diaspora that unfold until today, structuring ethics, epistemologies and hegemonic narratives.